Implants in the zygomatic bone for maxillary prosthetic rehabilitation: a systematic review - Goiato, Marcelo Coelho [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Moreno, A. [UNESP]; Gennari-Filho, H. [UNESP]; Santos, Daniela Micheline dos [UNESP]; Santiago, J. F. [UNESP]; Santos, E. G. dos (Churchill Livingstone, 2014)
The purpose of this systematic review was to evaluate clinical studies on the follow-up survival of implants inserted in the zygomatic bone for maxillary rehabilitation. A comprehensive search of studies published from 2000 to July 2012 and listed in the PubMed/MEDLINE, Embase, and Cochrane Library databases was performed in accordance with the PRISMA statement. Relevant studies were selected according to predetermined inclusion and exclusion criteria. The initial database search yielded 751 titles. After filtering, 313 abstracts were selected, culminating in 42 full text articles. Application of eligibility criteria led to the elimination of 17 articles. Hence 25 full-text articles were considered clinically relevant and were included. Calculations of the interval survival rates and cumulative survival rates of implants could be carried out on the data extracted from the final list of included studies for the different time intervals. These studies reported the insertion of a total of 1541 zygomatic implants and 33 implant failures. Failure generally occurred during the first year interval and was related to clinical complications, such as recurrent acute and chronic sinusitis. After a 36-month follow-up, the survival rate was 97.86%. Additional studies with longer follow-up periods, including the number of zygomatic implants inserted and details of the variations in the surgical techniques used and the impact of the maxillary morphology are still required.
Keywords: zygomatic implants; follow-up; dental implants; edentulous maxilla